1997
DOI: 10.1002/eji.1830271034
|View full text |Cite
|
Sign up to set email alerts
|

Host cell factor CD59 restricts complement lysis of Plasmodium falciparum‐infected erythrocytes

Abstract: Here we demonstrate that components of the entire complement cascade are fixed on the surface of erythrocytes infected with the human malarial parasite Plasmodium falciparum. Despite the activation of lytic complement factors, no complement-mediated lysis of P. falciparum-infected erythrocytes occurred only in the absence of functional intrinsic CD59. These data suggest that the restriction of the complement attack of P. falciparum-infected erythrocytes is principally mediated by intrinsic host cell factors, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 31 publications
2
30
0
Order By: Relevance
“…The relatively small contribution of complement to this early stage of infection by the blood stage parasite is perhaps a consequence of the inefficiency of complement in mediating the lysis of parasite-infected cells (14,48). These data, taken together with studies demonstrating that antibody-mediated protection in nonlethal or lethal malaria models does not require Fc receptors (31,45), suggest that there is not a prominent role for either of the major opsonophagocytic systems in host defense against a primary blood stage malaria infection in mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relatively small contribution of complement to this early stage of infection by the blood stage parasite is perhaps a consequence of the inefficiency of complement in mediating the lysis of parasite-infected cells (14,48). These data, taken together with studies demonstrating that antibody-mediated protection in nonlethal or lethal malaria models does not require Fc receptors (31,45), suggest that there is not a prominent role for either of the major opsonophagocytic systems in host defense against a primary blood stage malaria infection in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Complement has been shown to be able to kill both human and rodent malaria parasites in vitro, at different stages in the life cycle, in the presence of specific antibodies (10,11,29). However, infected erythrocytes, in spite of their ability to activate complement, seem quite resistant to complement-mediated lysis, a phenomenon attributable in part to the presence of complement-regulatory proteins on the infected cells (14,48). Moreover, Plasmodium berghei sporozoites have been shown to be resistant to complement from their susceptible rodent hosts but not to human serum (15).…”
mentioning
confidence: 99%
“…We therefore investigated malarial infection and vacuolar uptake of raft markers in PNH cells as compared with normal cells. Previous studies have indicated that PNH cells are invaded by the malaria parasite (35,36). However, the issue of intraerythrocytic growth of the parasite within the vacuole and the uptake of DRM proteins and lipids during infection was not examined.…”
Section: Movement Of Erythrocyte Raft Proteins and Lipids Into A Malamentioning
confidence: 99%
“…CD59 is a principal regulatory protein of complement attack [17]. Weisner et al [28] found that despite the activation of all lytic complement factors, no complement-mediated lysis of RBC occurred in the presence of functional intrinsic CD59. Because CD59 levels do not change significantly during malarial anaemia, this probably limits complement-mediated lysis.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of complement occurs in a step-wise fashion, and each regulatory protein acts at a different step in the cascade. CD55 acts at the initial enzymatic step to prevent the activation of C3 to C3b by accelerating the dissociation of the C3 convertase C4-2a and C3bBb [28-30]. CD59 prevents formation of polymeric C9 complex at the final step of MAC assembly [31].…”
Section: Discussionmentioning
confidence: 99%